Evaluating the efficacy and impact of neutropenic diet in pediatric hematology patients: a longitudinal cohort study on adherence, clinical outcomes, and socioeconomic factors - Singh, Amitabh; Kushwaha, Neetu; Srishwan, Raja; Zaman, Shamsuz; George, Noreen Grace; Kamal, Raj; Swain, Sandeep Kumar; Kaur, Manpreet; Siraj, Fouzia; Sharma, Saurabh; Noor, Baseer; Prabhakar, Prashant; et al. (Frontiers in Nutrition, 2025)
Background and aimA neutropenic diet aims to reduce hospitalizations from febrile neutropenia and sepsis in pediatric hematology patients during chemotherapy. This study aimed to evaluate its effectiveness in improving mortality, morbidity, and overall outcomes while considering limitations, adherence rates, and its impact on hospital admissions and culture positivity.MethodA prospective 18-month observational study was conducted on pediatric hematology patients in a pediatric department at a tertiary care center. Using a baseline questionnaire at the introduction of a neutropenic diet, the study assessed the clinical history, diagnosis, clinicopathological parameters, dietary recommendations, and socio-demographic data of the patients. Patients were followed up for up to 1 year to evaluate diet adherence, outcomes, mortality, and morbidity, as indicated by hospital admissions for febrile neutropenia.ResultsAn analysis involving 100 patients was conducted to assess adherence to a neutropenic diet and its ramifications on clinical outcomes over a period of 18 months. Initial follow-up data were accessible for 83 patients, revealing an adherence rate of 66%, which subsequently declined to 57% following a 6-month interval. Patients were categorized as compliant or non-compliant, but no correlation was found between adherence and febrile admissions, sepsis, hospitalizations, or mortality. Among compliant patients, 62% showed sepsis signs, though only 19% had positive blood cultures in the whole study group. Non-adherence was linked to demographic factors such as large family size, financial constraints, and limited resources. The neutropenic diet showed minimal impact on morbidity and mortality.ConclusionOur study does not support the strict adherence to the neutropenic diet, as there is no evidence of reduced infections and the dietary adherence also imposes an undue financial burden on patients. Instead, focusing on the safe acquisition of food, food processing, and proper hand cleanliness will probably provide superior protection against infection.